Chemical Constituents and Anti-Inflammatory Effect of Incense Smoke from Agarwood Determined by GC-MS - De-Qian Peng; Zhang-Xin Yu; Can-Hong Wang; Bao Gong; Yang-Yang Liu; Jian-He Wei (International Journal of Analytical Chemistry)
Agarwood is generally used to make incense sticks in China and Southeast Asia. It emits smoke with a pleasant odor when burned. There are few reports on the chemical components of smoke generated by burning or heating agarwood. The agarwoods were produced by the whole-tree agarwood-inducing technique (AWIT), agarwood induced by axe wounds (AAW), burning-chisel-drilling agarwood (BCDA), wood of Aquilaria sinensis trees (AS), respectively. Herein, we used GC-MS to analyze the chemical constituents of incense smoke generated from AWIT, AAW, BCDA, AS, and the extracts of sticks from agarwood produced by the whole-tree agarwood-inducing technique (EAWIT), and 484 compounds were identified. A total of 61 chemical constituents were shared among AWIT, AAW, and BCDA. The experimental data showed that aromatic compounds were the main chemical constituents in agarwood smoke and that some chromone derivatives could be cracked into low-molecular-weight aromatic compounds (LACs) at high temperature. Furthermore, agarwood incense smoke showed anti-inflammatory activities by inhibiting lipopolysaccharide- (LPS-) induced TNF-α and IL-1α release in RAW264.7 cells.